Construction and simulation of fiber optic stress wave sensing system based on wavelet packet-lamb wave damage imaging - X.L. Li; F. Liu; Q.N. Hui (Компьютерная оптика)
Nowadays, various materials are extensively utilized in various fields. These materials often cause invisible damage with the long-term service of machines. A health monitoring system for materials was presented to eliminate safety hazards as much as possible. This study proposed a fiber optic stress wave sensing system in view of Lamb wave damage imaging to address the limitations in the use of materials in some flaw detection systems. Meanwhile, Lamb waves with small propagation attenuation and long distance in the material were selected as the detection method. Then the fiber optic stress wave sensing system was used to carry out damage imaging. The imaging principle of wavelet packet decomposition was selected to avoid losing low-frequency information. The experiment demonstrated that compared to the original method in view of time correlation coefficient, the method used in this study improved the signal-to-noise ratio of damaged images by 1.0112 dB, higher accuracy, better imaging quality, and more pronounced output images. This research offers a theoretical foundation for the application of fiber optic stress wave sensing systems in the flaw detection, provides practical value for the practical application of Lamb waves, and has positive significance for the application of flaw detection in industry.